2019
DOI: 10.3390/rs11151744
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Total and Inorganic Suspended Sediments in Amazon Floodplain Lakes: A Multisensor Approach

Abstract: Remote sensing imagery are fundamental to increasing the knowledge about sediment dynamics in the middle-lower Amazon floodplains. Moreover, they can help to understand both how climate change and how land use and land cover changes impact the sediment exchange between the Amazon River and floodplain lakes in this important and complex ecosystem. This study investigates the suitability of Landsat-8 and Sentinel-2 spectral characteristics in retrieving total (TSS) and inorganic (TSI) suspended sediments on a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 120 publications
(259 reference statements)
3
23
0
1
Order By: Relevance
“…It is noteworthy that R 2 values are not high, which could be explained by the time differences between in situ data and satellite overpass as well as by the low variability in R rs values for each band. When the bands were analyzed separately (Table 7), it was noticeable that glint correction improves the accuracy for NIR MSI bands (reduction of up to 20% in MAPE values, expected for B05), corroborating with previous studies [79]. MAPE values for glint correction using MSI B11 were lower than 29% for all bands except for B08.…”
Section: Atmospheric Correction Evaluation and Oha Image Validationsupporting
confidence: 87%
See 3 more Smart Citations
“…It is noteworthy that R 2 values are not high, which could be explained by the time differences between in situ data and satellite overpass as well as by the low variability in R rs values for each band. When the bands were analyzed separately (Table 7), it was noticeable that glint correction improves the accuracy for NIR MSI bands (reduction of up to 20% in MAPE values, expected for B05), corroborating with previous studies [79]. MAPE values for glint correction using MSI B11 were lower than 29% for all bands except for B08.…”
Section: Atmospheric Correction Evaluation and Oha Image Validationsupporting
confidence: 87%
“…When the bands were analyzed separately (Table 7), it was noticeable that glint correction improves the accuracy for NIR MSI/Sentinel-2 band (reduction of up to 20% in MAPE values, expected for B05), corroborating with previous studies [79]. MAPE values for glint correction using MSI/Sentinel-2 B11 were lower than 29% for all bands except for B08.…”
Section: Atmospheric Correction Evaluation and Oha Image Validationsupporting
confidence: 86%
See 2 more Smart Citations
“…L8SR uses an internal algorithm to provide the user with a product with atmospheric correction. The correction used in L8SR is based on the 6SV (Second Simulation of the Satellite Signal in the Solar Spectrum-Vector Version) [19,20] and several authors demonstrated the accuracy of such correction for different targets worldwide, such as vegetation [21,22] and water [23].…”
Section: Plos Onementioning
confidence: 99%